The Dilemma of Breast Cancer Treatment and Existing Collagen Vascular Disease: A Case of Scleroderma and Review of the Literature. Issue 4 (28th April 2016) - Zaremba, Nicole M.; Tamkus, Deimante; DiCarlo, Luciano; Herman, James; Martin, Mersadies; Bumpers, Harvey L.
Abstract: Collagen vascular diseases present a treatment dilemma for patients with breast cancer. Due to the potential for severe, acute, and late complications of radiation therapy, a history of collagen vascular disease (CVD) is a relative contraindication to breast‐conserving treatment. We present a case of early stage breast cancer in a patient with severe scleroderma treated with breast‐conserving surgery without radiation and a brief review of the published literature regarding the therapeutic approach to the patient with CVD and breast cancer.